2014
DOI: 10.1016/j.ecoleng.2014.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of partially saturated vertical-flow constructed wetland with trickling filter and chemical precipitation for domestic and winery wastewaters treatment

Abstract: The use of Vertical Flow Constructed Wetlands (VFCW) is growing rapidly in Europe for domestic wastewater treatment in small communities. In order to improve denitrification and dephosphatation as compared to classical VFCW, the Azoé-NP ® process has been developed. The process line consists of: a biological aerobic trickling filter as a primary treatment stage, ferric chloride (FeCl 3) addition for phosphorus (P) treatment and two stages of partially saturated VFCW. A municipal wastewater treatment plant usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 22 publications
1
28
1
2
Order By: Relevance
“…Most of them are composed of two-stages of vertical flow constructed wetlands (VFCWs) in series, but many configurations exist (association with horizontal flow, pond systems or conventional treatment systems, one stage of vertical flow with recirculation, partially saturated systems, etc.) (Aguilera Soriano et al, 2011;Prost-Boucle and Molle, 2012;Kim et al, 2014;). Current practice usually involves two treatment stages, with three units in parallel on the first stage and two for the second, with successive periods of feeding (3.5 days), and rest periods (7 days at the first stage and 3.5 at the second stage) to maintain permeability, oxygen content and to control the biomass growth (Liénard et al, 1990a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are composed of two-stages of vertical flow constructed wetlands (VFCWs) in series, but many configurations exist (association with horizontal flow, pond systems or conventional treatment systems, one stage of vertical flow with recirculation, partially saturated systems, etc.) (Aguilera Soriano et al, 2011;Prost-Boucle and Molle, 2012;Kim et al, 2014;). Current practice usually involves two treatment stages, with three units in parallel on the first stage and two for the second, with successive periods of feeding (3.5 days), and rest periods (7 days at the first stage and 3.5 at the second stage) to maintain permeability, oxygen content and to control the biomass growth (Liénard et al, 1990a, b).…”
Section: Introductionmentioning
confidence: 99%
“…1. This experimental setup is meant to simulate the operational units of a real-scale AZOE-NP 1 plant but focused only on the first stage of filters as previous studies had shown that the efficiency of the process mainly occurred within the 1st stage (Kim et al, 2014).…”
Section: Description Of Pilot's Designmentioning
confidence: 99%
“…The treatment plants differed by the implementation or not of stages 2 and 3, as detailed in Table 1. The operating conditions of the plants were described in more details in previous articles (Kim et al, 2013;Kim et al, 2014). The selected plants differed not only by the operations in the treatment chain ( Figure 1 and Table 1) but also with respect to other parameters, such as the number of years of operation, the nominal capacity, the peak flow, the total area of VFCW stages (Table 1), and other environmental factors.…”
Section: Sites Of Investigationmentioning
confidence: 99%